Portrayal of Power in the Headlines of Pakistani English Newspapers: A Pragmatic Stylistic Analysis - Mehreen, Sundas; Rasul, Sarwet; Akhtar, Yasmin (Journal of Communication and Cultural Trends, 2024)
In the present information age, media texts play a dual purpose of transmitting information as well as being a decisive factor to develop public opinions by creating relevant discourse as per the demand of those with particular interests. Such a situation necessitates a critical inquiry into media texts to desensitize the readers to avoid taking media texts at face value. However, the complex nature of such texts requires multi-perspectivism which is made possible through interdisciplinary studies (Hansen, 2011; Klein, 2004). The pragmatic stylistic framework developed by Black (2006), a combination of two domains, provides us with the tools to disentangle the intricacies of such texts and to read between the lines. In the same vein, the present study utilizes Black’s (2006) pragmatic stylistic framework to identify the linguistic and stylistic strategies and also to explore how the language resources are manipulated and used as a tool to depict the interplay of power relations based on difference in position, authority or situation. The data for the current pursuit comprises 30 front-page headlines from The Daily Dawn and The News International. The data analysis process follows the analytical paradigm of descriptive qualitative interpretation in conjunction with Black’s pragmatic stylistic framework (2006). The findings of the study reveal a significant role played by the pragmatic stylistic features in creating and maintaining power relations in newspaper headlines. The findings further validate that linguistic resources are exploited in a way to influence readers’ perception of the reported event and to implicitly project newsmakers’ ideologies. The findings highlight the need to sensitize the readers to such linguistic manoeuvres in order to help them avoid taking the media texts at face value.